The Principle of Judicial Specialization in Commercial Disputes in Algeria: Between Achievements and Limitations - Ould Mohamed, Mohand Cherif (Journal of Legal Studies and Researches, 2026)
The establishment of specialized commercial courts reflects a step toward enforcing judicial specialization in commercial matters. Assigning certain disputes to these courts and requiring prior conciliation supports this approach. Yet, limiting their jurisdiction and the absence of a specialized appellate court weakens its scope and hinders coherent commercial jurisprudence.